0641 Effects of Weight Loss During Long-Term Solriamfetol Treatment on Cardiometabolic Indices. (27th May 2020) - Malhotra, A; Strollo, P; Pepin, J; Schweitzer, P; Lammers, G; Hedner, J; Redline, S; Chen, D; Chandler, P; Bujanover, S; Menno, D; Strohl, K
Abstract: Introduction: Increased prevalence of obesity has been reported in patients with narcolepsy and obstructive sleep apnea (OSA). Results from a 1-year open-label extension (OLE) study showed ≥5% weight loss in 4.5%, 17.3%, and 32.4% of participants with narcolepsy or OSA receiving solriamfetol 75, 150, or 300mg/d. We examined whether clinically significant weight loss (≥5%) in this population had favorable effects on biomarkers of cardiometabolic risk compared to no such weight loss. Methods: We evaluated changes in weight and BP (parent study baseline to OLE week 40) and clinical laboratory assessments (OLE baseline to week 40) in participants with narcolepsy (n=124) or OSA (n=250) from the OLE study. Results: Of 374 participants, 96 (25.7%) had ≥5% weight loss and 34 (9.1%) had ≥5% weight gain. Demographics were similar in those with and without (n=278) ≥5% weight loss. From baseline to week 40, among participants with weight loss, there were decreases in percentage with high (ie, >ULN) serum glucose (36.6% to 28.1%) or triglycerides (26.6% to 21.9%), whereas among participants without weight loss, there was an increase in percentage with high glucose (43.3% to 50%) and no change in percentage with high triglycerides (37.1% to 37.2%). The percentage of participants with high total cholesterol was stable among participants with weight loss (22.3% to 22.9%) and increased (32.7% to 37.2%) in participants without weight loss. Participants with weight loss had mean±SD reductions in SBP (-2.6±11.4mmHg) and DBP (-1.0±9.0mmHg), whereas participants without weight loss had increases of +0.65±12.5mmHg and +1.2±8.7mmHg, respectively. Conclusion: Among solriamfetol-treated participants with ≥5% weight loss, there were decreases in BP and percentage of participants with high glucose and triglycerides. Further research is required to examine prospective long-term effects of solriamfetol on specific biomarkers of cardiometabolic risk. Support: Jazz Pharmaceuticals